2020
DOI: 10.21203/rs.2.17377/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The relationship between symptom burden and systemic inflammation differs between male and female athletes following concussion.

Abstract: Background: Inflammation appears to be an important component of concussion pathophysiology. However, its relationship to symptom burden is unclear. Therefore, the purpose of this study was to evaluate the relationship between symptoms and inflammatory biomarkers measured in the blood of male and female athletes following sport-related concussion (SRC). Results Forty athletes (n = 20 male, n = 20 female) from nine interuniversity sport teams at a single institution provided blood samples within one week of an … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…Sex can be an important factor in inflammation pathophysiology. In athletes who suffered a concussion, while men have a positive correlation of IFN- γ levels with the severity of their symptoms, women have a negative correlation of IFN- γ levels and symptom severity [ 44 ]. However, apart from a slight difference in healthy individuals, sex was not a factor that could interfere with IFN- γ production after stimulus with EVs from chronic Chagas disease patients.…”
Section: Discussionmentioning
confidence: 99%
“…Sex can be an important factor in inflammation pathophysiology. In athletes who suffered a concussion, while men have a positive correlation of IFN- γ levels with the severity of their symptoms, women have a negative correlation of IFN- γ levels and symptom severity [ 44 ]. However, apart from a slight difference in healthy individuals, sex was not a factor that could interfere with IFN- γ production after stimulus with EVs from chronic Chagas disease patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although IL-1b has several important physiological roles, multiple studies have reported that elevated brain levels of this cytokine can be a key contributor to mTBI out-comes. [28][29][30] A number of studies have attempted to quantify circulating IL-1b following concussion; however, these studies are commonly plagued by undetectable levels of circulating IL-1b, 24,[31][32][33] As such, IL-1b is frequently unreported in studies investigating fluid biomarkers of concussion. Two studies have quantified and reported opposing findings for IL-1b acutely following concussion.…”
Section: Chronic Il-1b Changes Following Concussion 1353mentioning
confidence: 99%